The ability and competence vocabulary: Some neopragmatic considerations (Cadernos de Psicologia Social do Trabalho, 2001)
The aim of this paper is to present and discuss some of the main components of ability and competence vocabulary. Starting from a theoretical ransom of concepts comprised in the neopragmatic philosophy of language it is proposed that such vocabulary is characterized as a discursive structure articulated by the notion of personality, individual action, performance and by the notion of learning society, that is to say, by the idea of a society gone back to the continuous knowledge and learning. The paper still develops the argument that the ability and competence vocabulary institutes certain ways of life that, in function of its repetition and reiteration, begin to represent unquestionable and natural modalities of mechanisms of subjective formation, in a time in which the wide identity narratives lose their consistency, comprehending, among others, the loss of class and collective narratives - as they were articulated around the Welfare State policy - and the corrosion of work society (the end of the full employment).